The Correlation Between Listening Comprehension and Speaking Ability Among EFL Students - Hasan, Erna (Huele: Journal of Applied Linguistics, Literature and Culture, 2022)
This study aimed to investigate the correlation between listening comprehension and speaking ability among students at the English Department of Pattimura University, batch 2018. A quantitative correlational research design was employed, and data was collected through score documentation and a questionnaire. The findings revealed a positive and significant correlation between listening comprehension and speaking ability, with a correlation coefficient (r) of 0.608. The study concludes that listening comprehension is a crucial predictor of speaking ability and suggests that language teachers should provide ample opportunities for students to engage in listening activities to improve their overall speaking proficiency. Further research is recommended to explore other factors that may influence speaking ability beyond listening comprehension.